Risk of antidepressant initiation among users of cardiovascular agents and metformin. - Ivana Bojanić; Ottar Bjerkeset; Lana J. Williams; Michael Berk; Johan Håkon Bjørngaard; Erik R. Sund; Hege Sletvold (Wiley, 2023)
Abstract Cardiovascular disease and diabetes are risk factors for depression, yet the relationship between the drug treatments for these diseases and the risk of antidepressant initiation remains unclear. This study aimed to examine possible associations between the use of angiotensin II receptor blockers (ARBs), angiotensin‐converting enzyme inhibitors (ACEI), acetylsalicylic acid (ASA), beta‐blockers (BB), calcium channel blockers (CCB), diuretics, or metformin and risk of antidepressant initiation. The Trøndelag Health Study (HUNT3), Norway, was linked to the Norwegian Prescription Database (NorPD). Participants with no prescriptions of cardiovascular agents, metformin, or antidepressants for at least 6 months before HUNT3 (baseline) were eligible and followed for 10 years. The exposure was the use of cardiovascular agents or metformin, defined as mono‐ or polytherapy from baseline to end of follow‐up. The outcome was the initiation of antidepressant use, indicated by the first drug dispensation during the study period and expressed as hazard ratios (HRs) with 95% confidence intervals (CI). Among 20 227 adults aged 40-70 years at baseline, we observed different associations between cardiovascular agents or metformin and the risk of antidepressant initiation. ARBs or CCB monotherapy was associated with a lower risk of initiating antidepressant use (HR 0.70; 95%CI 0.56-0.88 and HR 0.81; 95%CI 0.61-1.06, respectively) compared to no use of any drugs included in the study (reference). Reduced risk of antidepressant initiation was among ASA or statin polytherapy users, whereas there was a small increased risk among participants on ASA monotherapy. In contrast, there was no statistical evidence of associations between ACEI, BB, diuretics, or metformin and increased or decreased risk of antidepressant initiation. Our mixed findings indicate the possibility that some cardiovascular agents may be associated with a reduced risk of initiating antidepressant use while others may not. However, bias due to the limitations of the study design is possible.